Indentification of the Streptomyces strain DN-05 producing antibiotics with wide activity isolated from the soil of the Quang Nam province - Ha, Do Thu (Academia Journal of Biology, 2015)
Indentification of the Streptomyces strain DN-05 producing antibiotics with wide activity isolated from the soil of the Quang Nam province